Manuk Abeghyan, a Distinguished Theorist of the Grammar of the Eastern Armenian Literary Language - Nersisyan, Bagrat (Bulletin of Yerevan University B: Philology, 2024)
The article addresses fundamental issues in the grammar of this language. Manuk Abeghyan, nearly a century ago, developed a scientifically grounded doctrine based on the logical and semasiological principles of linguistics, particularly focusing on the definition of a word and considering its semantics. In this regard, he treats participles and gerunds as separate words, that is, as verbal nouns and verbal adjectives. The voice of a verb is determined by contrasting transitivity and intransitivity. With the help of verbal infixes, new words are created and the voice of the verb changes, accordingly. In the paradigmatic series, he identifies five cases, and in the syntagmatic series, eight. This work is of great importance both in lexicology and in the grammar of the Eastern Armenian literary language. Renowned scholars E. Aghayan and G. Jahukyan, based on the theory of structural linguistics, developed M. Abeghyan’s theory in problematic areas concerning verbal nouns, verbal infixes, verbal moods, categories of voice and aspect, and the issues of the number of cases, etc. Unfortunately, the scientific achievements of these outstanding scholars have not found their rightful place in the normative grammar of the Eastern Armenian literary language.